PERALIHAN HAK ATAS TANAH UNTUK PEMBANGUNAN HOTEL DI KOTA BOGOR DALAM PERSPEKTIF PERUNTUKAN TANAH (STUDI KASUS HOTEL AMAROOSSA DI KOTA BOGOR) - Dian, Warizal Muhammad (DERECHTSSTAAT, 2017)
Implementation and Monitoring Land Use Permit Allotment for Development in the city of Bogor is to regulate the activities of land transition occurred in the city of Bogor. Therefore, this article will explain how to change the soil in the implementation of the Basic Building coefficient (KDB) and coefficient Building (KLB) in Bogor City Special construction Amaroossa Hotel? and How the construction of hotels in Bogor with consideration land use? Writing method using descriptive empirical laws. The results of the implementation and monitoring of land use designation permits in the city of Bogor is already done, but still a lot of ground breaking transition designation permits the use of land and it is influenced by changes in land that is not in accordance with applicable local regulations. Transfer of rights to land can be done through the purchase, exchange, grant, gift with a will, according to the customs administration and other acts that are intended to move the property. Changes in land use may occur in a systematic and non-systematic. Systematic changes occurred with marked by recurrent phenomenon, namely the type of land-use change at the same location. With establishment Hotels in controlling the utilization of space one of the instruments used is the allotment of land use permit (IPPT). With this permission entire land use changes are required to obtain permission from the government without exception. As stated glittering Bogor City Regional Regulation No. 2 of 2007 on Building Permits and Regional Regulation No. 8 of 2011 Bogor About Spatial Plan 2011-2031 Bogor City.